The Unaccountables. - McKelvey, Tara (American Prospect, 2006)
Although some of the 25,000 civilian contractors working for the U.S. military in Iraq may well have engaged in torture, they cannot be prosecuted for their crimes. According to many observers in Iraq, instances of contractor abuse are hugely underreported by victims and underinvestigated by the military, and the cases that are brought to court move forward very slowly—partly because it is not clear which laws can be applied to a nonmilitary person who commits a crime in a foreign jurisdiction. In real terms, this may mean that American employees, working alongside the U.S. military and on their payroll, have committed crimes in Iraq for which they will never be held accountable.